PENGARUH METODE INQUIRY DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA - Rossiana, Maya (Jurnal Tematik, 2018)
This study aims to find out: (1) Differences in science learning outcomes of students who are taught by the Inquiry Method and students' learning outcomes of science taught by Conventional methods; (2) Differences in science learning outcomes from students who have high learning motivation with students who have low learning motivation; and (3) Interaction between learning methods and learning motivation towards student science learning outcomes. The type of this research is quasi-experimental. The results of the study show that: (1) The students 'learning outcomes taught by the Inquiry Method are higher than the students' learning outcomes taught by Conventional methods (F count = 1.749> Ftable = 2.65); (2) There are significant differences between the learning outcomes of science students who have high learning motivation with students who have low learning motivation (F count = 1.351> Ftable = 2.64); and (3) There is an interaction between learning methods and learning motivation towards students' science learning outcomes (F count = 1.303> Ftable = 2.66).